2014
DOI: 10.1364/josaa.31.000312
|View full text |Cite
|
Sign up to set email alerts
|

Use of commercial off-the-shelf digital cameras for scientific data acquisition and scene-specific color calibration

Abstract: Commercial off-the-shelf digital cameras are inexpensive and easy-to-use instruments that can be used for quantitative scientific data acquisition if images are captured in raw format and processed so that they maintain a linear relationship with scene radiance. Here we describe the image-processing steps required for consistent data acquisition with color cameras. In addition, we present a method for scene-specific color calibration that increases the accuracy of color capture when a scene contains colors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 28 publications
0
75
0
Order By: Relevance
“…(6) We used a consumer-grade RGB camera mounted on a UAV to capture images in JPEG format, that provided simple digital number intensity values. Note that such data have an unknown relationship to scene radiance [53], and would be impacted by any changes in solar illumination during a survey. While we found that such imagery is suitable for separating broad and distinct classes, such as green vegetation and charred surface, more detailed vegetation characterization could benefit from using miniaturized multi-or hyper-spectral instruments that provide additional spectral information, and where radiance is normalized based on incident light sensors.…”
Section: Discussionmentioning
confidence: 99%
“…(6) We used a consumer-grade RGB camera mounted on a UAV to capture images in JPEG format, that provided simple digital number intensity values. Note that such data have an unknown relationship to scene radiance [53], and would be impacted by any changes in solar illumination during a survey. While we found that such imagery is suitable for separating broad and distinct classes, such as green vegetation and charred surface, more detailed vegetation characterization could benefit from using miniaturized multi-or hyper-spectral instruments that provide additional spectral information, and where radiance is normalized based on incident light sensors.…”
Section: Discussionmentioning
confidence: 99%
“…Following photography, each image was linearized with regards to light intensity based on camera responses to a set of eight Spectralon gray standards with reflectance values ranging from 2 to 99% (in custom programs written in Image J), because many cameras show non-linear responses in image value to changes in light levels that need to be corrected before accurate data can be obtained (see Westland and Ripamonti, 2004;Stevens et al, 2007a;Garcia et al, 2013). We also equalized the image values (Stevens et al, 2007a;Akkaynak et al, 2014) by removing the effects of varying light conditions with regards to the gray standard, and scaled each image channel (LW, MW, SW, and UV) to reflectance (where an image value of 255 on an 8-bit scale equals 100% reflectance). This gave us four images corresponding to the reflectance of each crab across the visible and UV spectrum, and provides the basis for color analysis independent of any specific visual system or predator group (Stevens, 2011), allowing us to analyze color change in terms of the physical properties of the crabs.…”
Section: Color and Brightness Quantificationmentioning
confidence: 99%
“…The raw digital counts can then be converted to reflectance values based on the regression equations between the actual reflectance measured from the tarpaulins and the digital counts extracted from the tarpaulins on each band image. Consumer-grade cameras can be used for scientific data acquisition if the image maintains a linear relationship to scene radiance [26] or if camera parameters (i.e., shutter speed, f-stop, and ISO-sensitivity) measuring scene radiance are used in conjunction with a camera calibration procedure [19].…”
Section: Image Acquisition Visualization and Preprocessingmentioning
confidence: 99%